Stepping Into an Equatorial Plasma Bubble With a Swarm Overfly - L. Spogli; L. Alfonsi; C. Cesaroni (Space Weather)
Abstract ESA's Swarm constellation entered in a “overfly” configuration in the period between September and October 2021, when the longitudinal distance between the lower pair and the upper satellite was at its minimum since the launch of the spacecrafts. In addition, the local time of the nighttime tracks was favorable to detect and study the morphology of post‐sunset equatorial plasma bubbles (EPBs). In this study, we focus on the Swarm overfly occurring between 00:41 UT and 00:59 UT on 30 September 2021, which covered one of the most densely instrumented regions for the study of the ionospheric irregularities embedded in the EPBs: the South American sector. By exploiting the use of ground‐based receivers of Global Navigation Satellite System (GNSS) signals in combination with the Swarm plasma density measurements, we study the irregularities in the EPB formed at ∼60°W and investigate the different scales of the irregularities and the cascading processes along the magnetic flux tubes. We also highlight how diffusion along the magnetic field lines occurs simultaneously with the plasma uplift, contributing then to the correct interpretation of the EPB evolution and decay process. The precious overfly conditions also allow the introduction of ionosphere‐related quantities, evaluated across the tracks at satellite altitudes enlarging the possibilities given by the same quantities already available along the tracks. Such opportunity envisages the possibility to proxy the impact of EPBs on GNSS signals with Low‐Earth Orbit satellite data provided by future missions specifically dedicated to the characterization of the near‐Earth environment and ionospheric studies.